Quelle alternative philosophique et éducative au consumérisme contemporain ? - Etienne Kola (Éducation et Socialisation)
The market is a central paradigm of contemporary economic intelligence. Adopted by the majority of the modern States, he has a spiritual shift in current humans making him a fanatic of consumption. The productivist and consumerist mechanics does not simply materialistic vision of the living? Does it not contribute to subvert human freedom? Isn't a factor of social and ecological imbalance; a vector of corruption of existential ethics? The designs of Emmanuel Levinas (1972) and Luc Ferry (1996) transcendence embody pedagogical virtues worthy to revolutionize current attitudes to the cult of materialism. Organized from a documentary operation, the reflection will be a critical analysis of consumerism, before being a plea in favour of the idea of transcendence such as promoted by Levinas and Ferry. Finally, it will highlight the contribution of the educational fact for one reform mindsets.